(untitled) - Martin, Terry R. (Boston, MA., 2004)
Human Anatomy and Physiology Laboratory Manual--Fetal Pig Dissection offers excellent, full color dissection photos of the fetal pig with matching corresponding labeled art. Web site activities found in numerous labs give students additional resources for learning. This laboratory manual contains sixty-two laboratory exercises and reports. The exercises illustrate and review anatomical and physiological facts and principles presented in an A&P textbook and help students investigate these ideas in greater detail.
Keywords: Human anatomy,Anatomy, Comparative,Swine,Human physiology; Laboratory manuals,Laboratory manuals,Fetuses,Dissection,Laboratory manuals,Laboratory manuals